Involvement of the Ventrolateral Prefrontal Cortex in Learning Others’ Bad Reputations and Indelible Distrust - Suzuki, Atsunobu; Ito, Yuichi; Kiyama, Sachiko; Kunimi, Mitsunobu; Ohira, Hideki; Kawaguchi, Jun; Tanabe, Hiroki C.; Nakai, Toshiharu (Frontiers in Human Neuroscience, 2016)
A bad reputation can persistently affect judgments of an individual even when it turns out to be invalid and ought to be disregarded. Such indelible distrust may reflect that the negative evaluation elicited by a bad reputation transfers to a person. Consequently, the person him/herself may come to activate this negative evaluation irrespective of the accuracy of the reputation. If this theoretical model is correct, an evaluation-related brain region will be activated when witnessing a person whose bad reputation one has learned about, regardless of whether the reputation is deemed valid or not. Here we tested this neural hypothesis with functional magnetic resonance imaging. Participants memorized faces paired with either a good or a bad reputation. Next, they viewed the faces alone and inferred whether each person was likely to cooperate, first while retrieving the reputations, and then while trying to disregard them as false. A region of the left ventrolateral prefrontal cortex, which may be involved in negative evaluation, was activated by faces previously paired with bad reputations, irrespective of whether participants attempted to retrieve or disregard these reputations. Furthermore, participants showing greater activity of the left ventrolateral prefrontal region in response to the faces with bad reputations were more likely to infer that these individuals would not cooperate. Thus, once associated with a bad reputation, a person may elicit evaluation-related brain responses on their own, thereby evoking distrust independently of their reputation.